Surveillance of resistant pathogenic E. coli from post-weaning diarrhea on intensive pig farms in Zhejiang province - JIANG Zhong-qi; CHEN Xiao-hong; FANG Wei-huan; ZHANG Ying-qin; SUN Jian-hua (浙江大学学报. 农业与生命科学版, 2004)
Antimicrobial susceptibility testing was performed on 60 clinical Escherichia coli isolates from pigs with post-weaning diarrhea in 10 intensive pig farms in Zhejiang province. The results showed that all the 60 pathogenic E. coli isolates have developed various degrees of resistances to 21 commonly used antimicrobials. 59 out of the 60 isolates exhibited resistances to 2 or more antimicrobials: 6 (10%), 11 (18.3%), 17 (28.3%), 17 (28.3%), and 9 (15.0%) of the 60 isolates were resistant to 1-3, 4-6, 7-9, 10-12 and 13-15 antimicrobial agents, respectively. Resistance percentage to 8 antimicrobial agents accounted for the highest (16.7%), followed by resistance percentage to 10 or 6 antimicrobials (15.0% and 11.7% respectively). Among the 60 isolates, there were 57 different resistant patterns; most of the isolates showed multiresistance and 4 of them were able to tolerate even 14 antimicrobials. Among the 21 commonly used antimicrobial agents, resistance occurred most frequently to SXT (sulfarmethox-azole/Trimethoprim) (88.3%), CM (Chloramphonicol) (81.0%), SM (Streptomycin) (78.3%), Ma (Maquindox) (77.3%), FD (Furazolidon) (75.0%), and HMQ (Olaquindox) (75.0%). Level of resistance to DAN (Danofloxacin), C1P (Ciprofloxacin) and NOR (Norfloxacin) was also high, the corresponding resistance frequency reached as high as 78.8%, 59.3% and 56.7%, respectively. The resistance frequency varies with districts and pig farms. It is noteworthy that the relatively new antibiotic FLO (Florfenicol) was 60.9% resistant in the study. It is therefore in urgent need to establish an effective surveillance system and to further study on antimicrobial resistance especially multiresistance of Escherichia coli.